Comparison of arterial versus venous parameters of Rotational thromboelastometry and multiple platelet function analyzer: Results of a pilot study. (October 2013) - Oswald, Elgar; Finsterwalder, Thomas; Innerhofer, Nicole; Haas, Thorsten; Mittermayr, Markus; Strohmaier, Susanne; Innerhofer, Petra
Abstract Background. In the operating room and at the ICU, Rotational thromboelastometry (ROTEM®) and multiple platelet function analyzer (Multiplate®) are frequently performed on arterial blood samples while known reference ranges refer to venous blood only. To evaluate whether there are clinical important differences between parameters measured in arterial and venous blood, we performed a prospective study in patients undergoing orthopedic surgery. Methods. Arterial and venous blood samples were drawn simultaneously after line insertion (T0), intraoperatively (T1), at the end of surgery (T2) and the INTEM®, EXTEM® and FIBTEM® ROTEM assays, as well as the ASPI®, ADP® and TRAP® assays were performed in arterial and venous samples using the ROTEM® and the Multiplate® device, respectively. Results. After informed consent, 52 patients were enrolled and data of 50 patients remained for final analysis. Venous and arterial measurement results correlated significantly with a coefficient of 0.519–0.977. At the three measurement points only a few statistically significant deviations were detected for some of the ROTEM® and Multiplate® parameters. The magnitude of differences was small and most likely without clinical relevance. Pathological conditions were detected with similar frequency regardless of the sampling site. Only Multiplate® TRAP at T0 indicated low platelet aggregation more frequently in venous than in arterial samples (p = 0.0455); however, values were only narrow below reference range. Conclusion. The observed differences between arterial and venous results were within the range of variability of the methods reported for venous blood. Pathological values that might be clinically relevant could be detected at similar rates regardless of the sampling site.